User Profile and Factors Correlating to Duration of Intrauterine Device Use - Gunardi, Eka R; Fadli, Fadli (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To determine the demographic and clinical profile of intrauterine device (IUD) users and factors correlating to duration of IUD use. Method: We conducted a prospective observational study of 867 patients who underwent IUD insertion in Raden Saleh Outpatient Clinic during the period of January - December 2011. All patients were followed for 1 year to ascertain any complaint of discharge after insertion. Spearman correlation test was conducted to inves- tigate the strength of correlation and significance between age, parity, and discharge, with duration of IUD use. Result: During year 2011, 867 patients (median of age=34 [range=14-49]; median parity=2 [range=0-7]) underwent IUD insertion in Raden Saleh Clinic. The majority of subjects were aged between 31-35 years old and were willing to use IUD for 4 years. Bivariate analysis revealed a significant correlation between age, parity, and vaginal discharge with duration of IUD use. The strongest correlation was identified between age and duration of use (r=0.25, p0.002 for parity and duration of use; r=0.05 p=0.045 for discharge and duration of use). Conclusion: Most IUD users were aged 31-35 years, who were willing to use IUD for 4 years. Factors that correlated with duration of IUD use were age, parity, and vaginal discharge. Keywords: contraceptive, duration of use, family planning, intrauterine device